Middle‐ear dexamethasone delivery via ultrasound microbubbles attenuates noise‐induced hearing loss. (27th December 2018) - Shih, Cheng‐Ping; Chen, Hsin‐Chien; Lin, Yi‐Chun; Chen, Hang‐Kang; Wang, Hao; Kuo, Chao‐Yin; Lin, Yuan‐Yung; Wang, Chih‐Hung
Abstract : Objectives/Hypothesis: In this study, we expanded our previous investigation by testing the efficiency of trans–round window membrane dexamethasone (DEX) delivery mediated by ultrasound (US)‐aided microbubbles (MBs) and its preventive effects regarding noise exposure in animal models. Study Design: Live animal model. Methods: Forty‐two pigmented male guinea pigs were divided into the following three groups: an US‐MBs (USM) group, in which the tympanic bulla was filled with DEX and MBs and exposed to US; a round window soaking (RWS) group, without the US irradiation; and a control group. The above‐mentioned manipulations were performed 2 hours prior to white noise exposure. The cochlear damage, including auditory threshold shifts, hair cell loss, and expression of cochlear HMGB1, was evaluated. Results: The enhanced DEX delivery efficiency of the USM group was approximately 2.4× to 11.2× greater than that of the RWS group. After the noise exposure, the RWS group showed significant cochlear protection compared with the control group, and more significant and dominant protective effects were demonstrated in the USM group. Conclusions: The application of US‐MBs provides a safe and more effective approach than spontaneous diffusion, which is commonly used in clinical practice; thus, this technique holds potential for future inner‐ear drug delivery. Level of Evidence: NA Laryngoscope, 129:1907–1914, 2019